Catalogue of oribatid mites (Acari: Oribatida) from Vorarlberg (Austria) - Schatz, Heinrich (Zootaxa, 2020)
A checklist of the oribatid mites from Vorarlberg (Austria) which covers all published records and hitherto unpublished results of additional collecting is presented. Several species are revised, doubtful and erroneous records from previous publications are discussed and corrected. At present a total of 327 described species are known from Vorarlberg, complemented by three subspecific taxa and two undetermined or undescribed species, altogether from 61 families. A total of 96 species (including 3 subspecific taxa) are newly reported from Vorarlberg, among them 16 species are new records for Austria. The compilation includes the occurrence of each species in different vegetation units and habitats of Vorarlberg, their known distribution in Austria and the neighbouring Alps, Switzerland and Southern Germany, as well as their general distribution. Occasional additional remarks give taxonomic and other information. A historical overview of the exploration of the oribatid mites in Vorarlberg is outlined. The general distribution of the oribatid mite fauna of Vorarlberg is analysed. Remarkable results are, among others, the findings of some mostly rare species which were described by Schweizer and Mahunka & Mahunka-Papp from Switzerland as well as species restricted to the Alps, mainly in higher montane regions.